2006
DOI: 10.1002/cpp.496
|View full text |Cite
|
Sign up to set email alerts
|

The probability of treatment success, failure and duration—what can be learned from empirical data to support decision making in clinical practice?

Abstract: Empirical methods have been found to be superior to clinical judgment for the purpose of correctly identifying patients at risk for treatment failure and, hence, to enhance psychotherapy outcomes. The development and evaluation of an empirical approach aimed at supporting clinical decisions during the course of psychotherapy is described. The tool provides predictions based on a patient-specific sampling strategy called the nearest neighbors method and on growth curve approaches to model an expected treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 33 publications
4
70
0
3
Order By: Relevance
“…Finch et al [13] developed and tested the accuracy of predicting deterioration in adults. These and related signal alarm systems have been evaluated in a number of empirical investigations [14,15,16,17]. This research shows that 85-100% of patients who deteriorate in treatment can be accurately identified prior to departing from treatment and often after the first few sessions of treatment.…”
Section: One Necessary Component Of Maximizing Patient Outcomementioning
confidence: 99%
“…Finch et al [13] developed and tested the accuracy of predicting deterioration in adults. These and related signal alarm systems have been evaluated in a number of empirical investigations [14,15,16,17]. This research shows that 85-100% of patients who deteriorate in treatment can be accurately identified prior to departing from treatment and often after the first few sessions of treatment.…”
Section: One Necessary Component Of Maximizing Patient Outcomementioning
confidence: 99%
“…Źródłem informacji o efektach psychoterapii mogą być pacjenci, psychoterapeuci, rezultaty testowych badań itd. (Fila, 1993;Grzesiuk, 2006;Lutz i in., 2006). Kryterium skuteczności terapii może być np.…”
Section: Doświadczenia Pacjenta Z Przebiegu Psychoterapii a Jej Skuteunclassified
“…Spolu s tím je pak možno vypočítat i pravděpodobnost, s jakou bude terapie pro daného klienta úspěšná (Castonguay et al, 2013). Pokud se skutečná trajektorie odchyluje od té očekávané v pozitivním směru, zvyšuje se pravděpodobnost úspěšné terapie, zatímco odchylky negativním směrem zvyšují riziko neúspěchu (Lutz et al, 2006). Empirický přístup se ukazuje jako účinnější než racionální (tamtéž), lze jej ale použít až ve chvíli, kdy v databázi daného systému existuje dostatečný počet dříve léčených klientů.…”
Section: Systémy Monitorující účInnost Psychoterapie V Běžné Praxiunclassified